Anticipating The Future: The Paradigm Of Foster Care In Society - Lasaiba, Djamila (JENDELA PENGETAHUAN, 2023)
The dynamic and rapidly changing development of modern society has transformed the paradigm of foster care from traditional to more inclusive, flexible, and child-centered approaches. This paper discusses this shift, identifies influencing factors, and outlines its impacts and implications within society. The effects of urbanization, changing work patterns, and shifts in societal values on the role of foster caregivers are elaborated in detail. The traditional paradigm of foster care, involving nuclear families and gender roles, is also analyzed. Subsequently, the transition towards a future paradigm that is more inclusive, flexible, and child-centered is presented, emphasizing the roles of technology, education, and collaboration between biological parents and extended families. Despite the challenges and obstacles in adopting this new paradigm, community collaboration in supporting education and understanding, along with real-world examples of successful community transitions, indicate positive potential in nurturing foster children. In conclusion, this new paradigm necessitates improved understanding, close collaboration, education, and skill development to create an environment that supports the academic, social, and emotional growth of foster children in an ever-evolving society